DAGESTAN OF THE LATE EMPIRE PERIOD IN THE WORKS OF E.M. DALGAT - Kudaeva, Svetlana Grigor'evna (History, Archeology and Ethnography of the Caucasus, 2021)
The article is devoted to the famous Dagestani historian, doctor of historical sciences, professor Dalgat Elmira Murtuzalievna. An attempt has been made to show the main milestones in the formation of Dalgat E.M. as a scientist. All her scientific activities are connected with the study of one of the most difficult periods in the history of Dagestan - the second half of the 19th - early 20th centuries, i.e. period of the late empire. Within this chronological framework, a rather difficult and long period of the region's incorporation into the political, socio-economic and cultural spheres of the Russian state took place. The study of individual aspects of this multifaceted process was of great importance for the formation of an integral scientific conceptual scheme for the formation of the Russian state.The author of the article presents a brief analysis of the fundamental works of Elmira Murtuzalievna: The peasantry of Dagestan at the turn of the XIX-XX centuries; The landlord economy of Dagestan in the 2nd half of the 19th - early 20th centuries; City and urban life in Dagestan in the second half of the 19th - early 20th centuries. In these works, for the first time in Dagestan historiography, an attempt was made to comprehensively study various aspects of the socio-economic development of Dagestan during this period.The article shows the main research problems and the main conceptual conclusions that the author came to in the course of their study. It is noted that relying on a fairly extensive source base, E.M. Dalgat managed to consider various aspects of the socio-economic and cultural development of Dagestan.The analysis of the content of the works made it possible to conclude that Elmira Murtuzalievna has a high level of theoretical training, which contributed to a deep scientific study of the factual material, provided reasoning for the conclusions and significantly expanded the range of vision of the problems under study. Monographs by E.M. Dalgat occupy a worthy place among fundamental Dagestan studies and, without a doubt, the findings are a significant contribution to the development of Russian Caucasian studies.
Keywords: Russia; Dagestan; the late empire period; Elmira Murtuzalievna Dalgat